Lignocellulosic biorefineries: The current state of challenges and strategies for efficient commercialization. (September 2021) - Usmani, Zeba; Sharma, Minaxi; Awasthi, Abhishek Kumar; Lukk, Tiit; Tuohy, Maria G.; Gong, Liang; Nguyen-Tri, Phuong; Goddard, Alan D.; Bill, Roslyn M.; Nayak, S.Chandra; Gupta, Vijai Kumar
Abstract: Lignocellulosic biomass is the most abundant and sustainable feedstock available globally. As a source of the polysaccharides, cellulose and hemicellulose, it can be converted into biofuels and other platform chemicals. This article highlights some important aspects that needs to be focused upon for the commercial development of lignocellulosic biorefineries. Although, lignocellulosic biomass offers clear value in terms of its green advantages and sustainability, there has been very low commercial success at industrial production levels. This can be attributed to a few key factors such as an irregular biomass supply chain, inefficient or complex pre-treatment and saccharification technologies, and scale up challenges leading to high capital and operating expenditures. Moreover, techno-economic studies performed on lignocellulosic biorefineries have revealed that process complexity is the most detrimental factor prohibiting scale-up. Although there have been several research efforts funded both by the public and private sectors, biomass valorization into biofuels and chemicals remains a technical and economical challenge. This review examines the global drivers towards the advancements of lignocellulosic biorefineries, technical and operational challenges for industrialization and future directions towards overcoming them. Highlights: Commercialization of lignocellulosic biomass refineries needs efficient value chain. Sustainable feedstock supply can be gained with biomass source diversification. New pre-treatment technologies can enhance yield and accelerate industrial scale-up. Novel enzyme cocktails can improve extraction and hydrolysis of polysaccharides. Industrial scale-up requires development of efficient co-processing techniques.